Data-Driven Bitext Dependency Parsing and Alignment - Martin Haulrich (Copenhagen Business School (CBS), 2012)
Parallel treebanks have received increasing attention in the past few years, primarily due to their potential use in statistical machine translation. Creating parallel treebanks manually is a time-consuming and expensive task and for this reason there is considerable interest in creating treebanks automatically. This task can be solved using standard tools such as parsers and aligners. However, because parallel treebanks are based on parallel corpora, we are in a special situation where the same meaning is represented in two different ways. This thesis is about how we can exploit this information to create better parallel treebanks than we can by using standard tools....
hdl:10398/8385
Keywords: 650